Unmet needs in the management of migraine in Greece from the perspective of medical experts: a Delphi consensus - Kourlaba, Georgia; Vikelis, Michail; Karapanayiotides, Theodoros; Solakidi, Argyro; Trafalis, Dimitrios; Lioliou, Katerina; Andriopoulos, Panagiotis; Panagiotou, Aspasia; Mitsikostas, Dimos-Dimitrios (Frontiers in Neurology, 2025)
IntroductionMigraine is a chronic, debilitating neurological disorder affecting billions worldwide. While not life-threatening, migraine patients experience significant unmet needs in diagnosis and management. Addressing these challenges could result in improvement of patient outcomes and reduction of the socioeconomic burden migraine imposes on individuals, healthcare system and the society.ObjectiveThis survey aimed to capture in Greece the perspective of medical experts (neurologists) specializing in migraine management regarding the socioeconomic burden of migraine and the unmet needs in diagnosis and treatment.MethodsAn online Delphi-based survey was conducted with 13 neurologists, experts in migraine. The survey consisted of 55 statements derived from literature research, regarding the burden of disease, diagnosis, treatment and unmet needs. Participants’ level of agreement for each statement was measured through a 5-point Likert scale (“Strongly Agree,” “Agree,” “Neither Agree nor Disagree,” “Disagree” and “Strongly Disagree”). Three rounds of voting were conducted to achieve consensus. The consensus threshold was set at 70% of responses, focusing on “Strongly Agree”/ “Agree” or “Disagree”/ “Strongly Disagree.”ResultsMost experts agreed on statements emphasizing on financial and social impact of the disease and its epidemiology. However, consensus was not reached on statements concerning patient preferences for treatment administration, treatment adherence, opioid use, and frequency of visits to neurologists. Consensus was reached on the need for better healthcare professional training and the development of effective, safe treatments.ConclusionThis survey highlighted the challenges of prompt diagnosis and effective management of migraine. Addressing these needs requires patient-centered approaches, enhanced healthcare-provider training, tailored therapeutic interventions, and advanced communication platforms.